Body Mind Therapy Improving Mental Health in Teenager - Daryaswanti, Putu Intan; Muryani, Ni Made Sri; Pendet, Ni Made Diah Pusparini (Babali Publisher, 2025)
Background: Mental health has become a critical concern among adolescents, particularly affecting their emotional regulation, problem-solving abilities, and interpersonal relationships. Middle school students are especially vulnerable as they navigate identity formation while being susceptible to external influences. Various factors, including peer pressure, media influence, and gender norms, can exacerbate the gap between adolescents' reality and future perceptions. This study aims to determine the effect of Body Mind Therapy on adolescent mental health. Methods: A quasi-experimental study with a one-group pretest-posttest design was conducted. The population comprised middle school students in the Puskesmas II Denpasar Utara area. The sample size was calculated using the Lemeshow formula (n=97), with final participants of 40 students selected through simple random sampling. Inclusion criteria were students aged 12-16 years with parental consent. Variables measured included vital signs (blood pressure, pulse, respiration), sleep quality (PSQI), anxiety (SAS/SRAS), and mental health (SDQ). Data were analyzed using a paired t-test with a 95% confidence interval. Results: Most of the adolescents were 14 years old (45%) and female (92.5%). After conducting a paired t-test, the results showed that diastolic blood pressure, pulse, respiration, sleep quality, and mental health variables in the difficulty component showed significant effects with a p-value < 0.05. Conclusion: This intervention can be relied upon to improve adolescents' physical and mental health, particularly in reducing physiological stress and improving aspects of mental health such as emotional difficulties.